O prazer na filosofia de Platão: algumas considerações a partir da leitura do Filebo - Barros, Leander Alfredo da Silva (2018)
This work aims to analyse the platonic conceptions around the theme of pleasure, notably those presented in the Philebus dialogue. I intend throughout the text to highlight some of the possible interpretations about the primordial question that surrounds the dialogue under analysis, which consists mainly in the reflection on the "good life" (βίον εὐδαιμονα). The thematic axis of our interpretative effort falls on the theme of pleasures and fundamentally on the ethical content presented during the work. For the exhaustive analysis of pleasure (ἠδονὴ), which occupies most of the discussion, results in an even more meaningful investigation around what should be elected as the "best kind of life" (γένος) by both interlocutors of this argumentative movement. The philosophical life which, perhaps, will characterize the lifestyle preferable to men, cannot disregard the relevance of pleasure, being in this case a “mixed life” (μεικτόν βίον), composed by pleasure (ἠδονὴ) and reflection (φρόνεσις). Therefore, if pleasures and knowledge seem to be present in the definition of the best kind of life: (i) the "calculation" of pleasures results in an important configuration of the scale of values relative to the constitution of mixed life; and, (ii) the very conception of the dialectic (a task pertinent to the philosopher), reaches an even more surprising and relevant meaning in the argumentation, that is, in defining itself as the fundamental reflexive exercise of "measure" (μέτρον) (between limited and unlimited) in human deliberations, and, by the way, aim at good and happiness.